Gut Microbiota: A Contributing Factor to Obesity - Harakeh, Steve M.; Khan, Imran; Kumosani, Taha; Barbour, Elie; Almasaudi, Saad B.; Bahijri, Suhad M.; Alfadul, Sulaiman M.; Ajabnoor, Ghada M. A.; Azhar, Esam I. (Frontiers in Cellular and Infection Microbiology, 2016)
Obesity, a global epidemic of the modern era, is a risk factor for cardiovascular diseases (CVD) and diabetes. The pervasiveness of obesity and overweight in both developed as well as developing populations is on the rise and placing a huge burden on health and economic resources. Consequently, research to control this emerging epidemic is of utmost importance. Recently, host interactions with their resident gut microbiota (GM) have been reported to be involved in the pathogenesis of many metabolic diseases, including obesity, diabetes, and CVD. Around 1014 microorganisms reside within the lower human intestine and many of these 1014microorganisms have developed mutualistic or commensal associations with the host and actively involved in many physiological processes of the host. However, dysbiosis (altered gut microbial composition) with other predisposing genetic and environmental factors, may contribute to host metabolic disorders resulting in many ailments. Therefore, delineating the role of GM as a contributing factor to obesity is the main objective of this review.Obesity research, as a field is expanding rapidly due to major advances in nutrigenomics, metabolomics, RNA silencing, epigenetics and other disciplines that may result in the emergence of new technologies and methods to better interpret causal relationships between microbiota and obesity.